MENINGKATKAN HASIL BELAJAR SISWA MELALUI PENERAPAN GAMIFIKASI QUIZIZZ PADA MATA PELAJARAN IPAS KELAS IV SD SWASTA HKBP TELADAN MEDAN - Karmila Bru Sebayang; Eni Yusnita Br Pardede; Eduard; Meldiya Sabrina Br Purba; Melan Hady Syari (STKIP Subang, 2026)
Low learning outcomes in elementary science and social studies remain a challenge, particularly when learning activities do not sufficiently involve interactive media that can enhance student participation. This study aimed to improve students’ learning outcomes through the implementation of Quizizz gamification in science and social studies learning for fourth-grade students at HKBP Teladan Private Elementary School Medan. This research employed a quantitative approach with an experimental method using a one-group pretest–posttest design. The subjects were 20 fourth-grade students who participated in four learning sessions. Data were collected through learning achievement tests, observation sheets, and interview guidelines. The test data were analyzed using descriptive statistics and a paired sample t-test at a 5% significance level. The results showed that students’ mean pretest score increased from 52.4 to 79.6 in the posttest, indicating an improvement of 27.2 points. The highest score increased from 65 to 88, while the lowest score increased from 40 to 70. The paired sample t-test result showed a significance value of 0.000 < 0.05, indicating a significant improvement in students’ learning outcomes after the implementation of Quizizz gamification. In addition, observation results showed that 85% of students demonstrated increased active participation during the learning process. Therefore, Quizizz gamification is effective as an interactive learning medium to improve students’ learning outcomes, motivation, focus, and engagement in elementary science and social studies learning.